A Difficulty Analysis of Cleft Sentences - Pelin Irgin (Informascope, 2013)
This empirical study was investigated to define how difficult the clefts sentences for the EFL freshman students and to describe the difficulty levels of types of cleft sentences. The study examined to what extend instruction on cleft sentences clarified the EFL freshman students' confusion in cleft structures. The data administrated by 61 freshman students at the Department of English Language Literature (ELL) in a state university in Turkey was collected through the pre-test and post-test design. The results revealed that participants showed a significant improvement in understanding the cleft structures. In addition, there are significant differences among students' level of recognition for each type of cleft structure and the most confusing cleft types for the EFL students are it-clefts, if-because cleft and all-cleft.